Photoprotection and vitamin D status. (1st November 2019) - Passeron, T.; Bouillon, R.; Callender, V.; Cestari, T.L.; Diepgen, T.; Green, A.C.; van der Pols, J.C.; Bernard, B.A.; Ly, F.; Bernerd, F.; Marrot, L.; Nielsen, M.; et al.
Summary: Vitamin D is produced by the skin in response to ultraviolet radiation (UVR) from sunlight. A lack of vitamin D, known as vitamin D deficiency, can cause bones to become soft and weak, which can lead to bone deformities. Whilst UVR exposure is a main source of vitamin D, it is also a primary cause of skin cancer, leading to debates on how to get the balance between ideal (sufficient) vitamin D levels and sun protection. This review aimed to offer practical recommendations on the impact of sunscreen use on vitamin D status. An international panel of thirteen experts in endocrinology, dermatology, photobiology, epidemiology and biological anthropology reviewed the literature relating to vitamin D levels and sunscreen use prior to a one day meeting in June 2017. They examined the current methods for assessing and determining vitamin D sufficiency, current public health recommendations, the impact of sun exposure on vitamin D and the effects of sunscreen use. There is no international agreement on the ideal vitamin D levels, with recommendations varying greatly. A blood level of ≥ 50 nmol/L 25(OH)D was the most widely held target level during this review. It was concluded that daily use of broad‐spectrum sunscreen (offering both UVA and UVB protection) will not affect vitamin D production in healthy people. However, people with photosensitive disorders are an exception to this and would therefore benefit from vitamin D screening as well as supplementation. Abstract : Linked Article: Passeron et al. Br J Dermatol 2019; 181 :916–931